2005
DOI: 10.1159/000087973
|View full text |Cite
|
Sign up to set email alerts
|

Locally Advanced Pancreatic Cancer Treated with Radiation and 5-Fluorouracil: A First Step to Neoadjuvant Treatment?

Abstract: Aim of the Study: In two institutions, a retrospective analysis was performed on patients with histologically proven locally advanced pancreatic cancer without distant metastases. The aim of this analysis is to assess whether chemoradiotherapy provides survival benefit for patients with locally advanced pancreatic cancer. Methods: Forty-five patients from the Erasmus Medical Centre (Erasmus MC), Rotterdam, received 5-fluorouracil (5-FU) and radiotherapy and, 38 patients from the Academic Medical Centre Amsterd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…4 The number of newly diagnosed patients nearly equals that of the deceased; no current treatment, whether surgical, chemotherapy or a combination thereof, results in an effective clinical response in more than 20% of patients and no treatment therapies have been found that extend survival beyond a few months. Clinically, pancreatic cancer presents in up to 50% at a locally advanced stage and, in up to 40% with metastatic disease, 5 dramatically reducing the chance of curative resection. Factors such as age, smoking, past medical history, and other conditions such as diabetes and pancreatitis have been associated risk factors of pancreatic cancer.…”
mentioning
confidence: 99%
“…4 The number of newly diagnosed patients nearly equals that of the deceased; no current treatment, whether surgical, chemotherapy or a combination thereof, results in an effective clinical response in more than 20% of patients and no treatment therapies have been found that extend survival beyond a few months. Clinically, pancreatic cancer presents in up to 50% at a locally advanced stage and, in up to 40% with metastatic disease, 5 dramatically reducing the chance of curative resection. Factors such as age, smoking, past medical history, and other conditions such as diabetes and pancreatitis have been associated risk factors of pancreatic cancer.…”
mentioning
confidence: 99%
“…On the other hand, our figures are higher than those reported by Smeenk et al . [ 7 ] who stated that only 42% (16 out of 38) of patients showed radiographic evidence of response (26% PR & 16% SD). This difference may result from the use of fluorouracil and not gemcitabine based chemoradiation in the reported series in constrast to our study, where gemcitabine based chemoradiotherapy was used.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to radiotherapy, results of clinical trials have been mixed, (1987; Klinkenbijl, Jeekel et al 1999; Neoptolemos, Stocken et al 2004; Smeenk, de Castro et al 2005; Stocken, Buchler et al 2005; Garofalo, Regine et al 2006; Sultana, Neoptolemos et al 2006; Saif 2007; Smeenk, van Eijck et al 2007; Artinyan, Hellan et al 2008) with divergent opinions concerning the same study being published. (Klinkenbijl, Jeekel et al 1999; Garofalo, Regine et al 2006) For this reason, radiotherapy continues to be viewed as an option to be reserved for research protocols and specialized centers.…”
Section: Discussionmentioning
confidence: 99%